Hematological indicator-based machine learning models for preoperative prediction of lymph node metastasis in cervical cancer - Zhao, Huan; Wang, Yuling; Sun, Yilin; Wang, Yongqiang; Shi, Bo; Liu, Jian; Zhang, Sai (Frontiers in Oncology, 2024)
Background Lymph node metastasis (LNM) is an important prognostic factor for cervical cancer (CC) and determines the treatment strategy. Hematological indicators have been reported as being useful biomarkers for the prognosis of a variety of cancers. This study aimed to evaluate the feasibility of machine learning models characterized by preoperative hematological indicators to predict the LNM status of CC patients before surgery. Methods The clinical data of 236 patients with pathologically confirmed CC were retrospectively analyzed at the Gynecology Oncology Department of the First Affiliated Hospital of Bengbu Medical University from November 2020 to August 2022. The least absolute shrinkage and selection operator (LASSO) was used to select 21 features from 35 hematological indicators and for the construction of 6 machine learning predictive models, including Adaptive Boosting (AdaBoost), Gaussian Naive Bayes (GNB), and Logistic Regression (LR), as well as Random Forest (RF), Support Vector Machines (SVM), and Extreme Gradient Boosting (XGBoost). Evaluation metrics of predictive models included the area under the receiver operating characteristic curve (AUC), accuracy, specificity, sensitivity, and F1-score. Results RF has the best overall predictive performance for ten-fold cross-validation in the training set. The specific performance indicators of RF were AUC (0.910, 95% confidence interval [CI]: 0.820–1.000), accuracy (0.831, 95% CI: 0.702–0.960), specificity (0.835, 95% CI: 0.708–0.962), sensitivity (0.831, 95% CI: 0.702–0.960), and F1-score (0.829, 95% CI: 0.696–0.962). RF had the highest AUC in the testing set (AUC = 0.854). Conclusion RF based on preoperative hematological indicators that are easily available in clinical practice showed superior performance in the preoperative prediction of CC LNM. However, investigations on larger external cohorts of patients are required for further validation of our findings.